Divergência genética entre acessos de coqueiro anão para caracteres morfológicos e agronômicos na baixada litorânea de Sergipe - Sobral, Kamila Marcelino Brito (2010)
Morphological characterization, performed by use of descriptors, identifies and describes the variability or diversity within and between accessions maintained in Germplasm Banks Assets. This information, provided for genetic resources studies may be used in improvement programs of coconut, especially when there are characteristics of interest to serve as matrices for production of hybrids or the selection of adapted or resistant varieties to certain factors. The study aimed to characterize and evaluate the dwarf accessions stored in the Active Germplasm Bank of Embrapa Coastal Boards, using a descriptive list drawn up by IBPGR in 1995, now Bioversity International. The experimental design was randomized block, with six treatments (accessions) and five replications, 16 useful plants /plot, spaced 7.5 x 7.5 x 7.5. It evaluated 11 useful plants of six accessions of Dwarf coconut: Green Dwarf Jiqui Brazil (DGeBrJ), Red Dwarf Cameroon (DRC), Red Dwarf Malaysia (DRM), Red Dwarf Gramame (DRG), Yellow Dwarf Gramame (DYG), Yellow Dwarf of Malaysia (DYM). Quantitative and qualitative descriptors, all data-related to vegetative, morphological and reproductive were considered. The genetic-statistical analysis was executed by SAS 9.1 and genes 2009 program. Data were submitted to ANOVA and the means of cultivars compared by Tukey test (5%) and genetic parameters (h2, CVg, and CVe Iv) were estimated. Genetic divergence between genotypes was quantified by Standardized mean Euclidean distance. The clustering methods used to group the genotypes were the UPGMA, the Tocher optimization and Main Components. With descriptors morpho-agronomics was possible to detect genetic divergence among accessions of the dwarf coconut germplasm bank. The UPGMA cluster analysis, Tocher and principal components demonstrated efficiency in the evaluation of the accessions. It was observed that characters like number of leaves, length of leaflets, width of leaflets, peduncle length, number of male flowers, number of floral branches, average length of floral branches, length of reproductive cycle, male reproductive phase duration, period between emergency and opening of inflorescences and number of inflorescence have high genetic variability, allowing success in improving of coconut using simpler selection methods such as mass selection. The AVeBrJ had the highest means to following characteristics: number of leaflets, length of leaflets, number of flower branches, length of reproductive cycle, male reproductive phase duration, showing a good vegetative and reproductive development.